Th17/Treg Cells and Inflammatory Factors in Patients with Thoracolumbar Kyphosis due to Ankylosing Spondylitis: Changes Before and After Vertebral Column Decancellation and Their Relationship with Sagittal Balance - Wang, Yan; Du, Jin; Wang, Tianhao; Xue, Chao; Zheng, Guoquan (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to explore the impact of Th17/Treg cell imbalance and inflammatory factors (IL-1β, IL-18, and TNF-α) on sagittal balance in patients with thoracolumbar kyphosis due to ankylosing spondylitis (AS) following vertebral column decancellation (VCD).Methods: A total of 134 AS patients undergoing VCD were enrolled and categorized into an imbalance group (46 cases) and a balance group (88 cases), depending on postoperative sagittal balance. Measurements of the Th17/Treg ratio and inflammatory factor levels were conducted at three time points: preoperatively (T0), 24 hours postoperatively (T1), and 4 weeks postoperatively (T2). These data were analyzed alongside sagittal parameters (SVA, PI-LL, and PT) to assess their correlations and predictive potential.Results: At 4 weeks after surgery, the imbalance group showed significantly elevated Th17/Treg ratios and higher levels of IL-1β, IL-18, and TNF-α compared to the balance group (P
Keywords: Ankylosing spondylitis; Th17/Treg, inflammatory factors; sagittal balance; vertebral column decancellation